Optimization of end-fire coupling between an LED mid-IR light source and SiNx optical waveguides for spectroscopic sensing - Pawaphat Jaturaphagorn; Nattaporn Chattham; Pichet Limsuwan; Papichaya Chaisakul (My University, 2021)
We design and optimize an optical coupling structure between a superluminescent light emitting diodes (SLED) and SiNx waveguides for the optical sensing, in which an efficient coupling between these waveguides is challenging due to significant cross-sectional difference. From FDTD investigation, we identify the coupling scheme that is suitable to directly couple light from a SLED into a relatively-thin SiNx waveguide suitable for optical sensing based on the evanescent field absorption. The coupling structure is systematically investigated and optimized in terms of refractive indices, coupler's geometrical parameters, and fabrication variations with corresponding detection performance. The coupling scheme could be instrumental in enabling the use of SLED technology in Si-based photonic integrated circuits for sensing applications.
Keywords: Waveguide; Photonic and Optical Devices